Software architecture impacts of big data - Berglund, Tim (O'Reilly Media, 2015)
"Tim Berglund will discuss how the commitment to distributed computing affects software architecture. We'll explore what happens with storage, computation, and coordination between servers in a distributed system. Distributed programming is different in almost every way from traditional, single-master programming, and in this webcast, we'll get an idea how those differences play out and what open-source products are current meeting the needs of the marketplace."--Resource description page.
Title from resource description page (viewed July 22, 2015)
Keywords: Software architecture; Electronic data processing -- Distributed processing; Architecture logicielle; Traitement réparti; Electronic data processing; Distributed processing